2017
DOI: 10.4183/aeb.2017.278
|View full text |Cite
|
Sign up to set email alerts
|

Increased Serum Level of FGF21 in Gestational Diabetes Mellitus

Abstract: Objective. Gestational diabetes mellitus (GDM) is a common endocrine complication in pregnancy. There are few risk factors that clearly correlate with GDM. Fibroblast growth factor 21 (FGF21) is a metabolic hormone that can regulate glucose metabolism. It has been recognized that serum levels of FGF21 are significantly increased in diabetes and insulin resistance states. The objective of this study was to determine the serum FGF21 levels in women with GDM compared with non-GDM women and its correlation with in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 16 publications
(16 reference statements)
3
13
0
Order By: Relevance
“…A meta-analysis of the nine articles was performed [12][13][14][15][16][17][18][19][20]. Data were all extracted as means ± SD, and significant heterogeneity existed in the studies (I 2 = 85%, p < 0.001, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A meta-analysis of the nine articles was performed [12][13][14][15][16][17][18][19][20]. Data were all extracted as means ± SD, and significant heterogeneity existed in the studies (I 2 = 85%, p < 0.001, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies found that the serum levels of FGF21 in GDM women were all elevated after 24 gestational weeks. Li et al and Bonakdaran et al found that GDM women had higher levels of FGF21 than NGT pregnant women at 24 to 28 gestational weeks (18,34). SǏMJÁK et al found that FGF21 in GDM women was higher than that in NGT pregnant women at 28 to 32 gestational weeks (35).…”
Section: Discussionmentioning
confidence: 98%
“…More interestingly, at the late 1st trimester, a reduction of plasma fetuin-A levels (and elevated hs-CRP) was also observed [121] (Table 3A). Another member of the FGF family, FGF-21, which induces the browning of white adipose tissue and acts as an upstream effector of adiponectin, was also expressed in placenta and increased in GDM women at the 24th week of gestation [148]. Also, afamin, a glycoprotein member of the albumin family expressed in liver and other peripheral tissues (i.e., placenta), may serve as an early (1st trimester) biomarker for pathological glucose and lipid metabolism during pregnancy [149].…”
Section: Prospective Diagnostic and Predictive Markers For Gdm With Amentioning
confidence: 99%
“…The sensitivity could have been limited by the variability and quality of samples and detection method, and specificity could have decreased since most biomarkers point out common diabesogenic processes (i.e., insulin resistance, inflammation). In this regard, FGF-21 [148, 169], visfatin [127, 170], IL-6 [119, 171] and resistin [128, 129] displayed variable levels depending on pregnancy phase, and afamin, among others, could serve also as a valid biomarker for other complicated pregnancies, like those with preeclampsia [149]. In this line, GDM patients with cardiovascular risk could be classified by testing biomarkers with key roles on cardiovascular pathophysiology.…”
Section: Limitations and Future Perspectivesmentioning
confidence: 99%